Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 1994
DOI: 10.1145/191666.191693
|View full text |Cite
|
Sign up to set email alerts
|

Distributed collaborative writing

Abstract: Previous research indicates that voice annotation helps reviewers to express the more complex and social aspects of a collaborative writing task. Little direct evidence exists, however, about the effect of voice annotations on the writers who must use such annotations.To test the effect, we designed an interface intended to alleviate some of the problems associated with the voice modality and undertook a study with two goals: to compare the nature and quantity of voice and written comments, and to evaluate how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 9 publications
0
17
2
Order By: Relevance
“…With a voice recording, message producers can leverage paralingual cues (e.g., inflection, pause timing, energy) for conveying equivocal and complex ideas [13]. Speech annotation/commenting, thanks to its rich, nuanced expressivity, has been widely adopted in different applications including online discussions [52] or document review [55]. Inspired by media richness theory [18] and the conceptual framework of deictic gestures [17], several multimodal annotation systems have tried to enrich communication and collaboration by combining multiple face-to-face inspired modalities, such as inking + speech [75,83], inking + gesture + speech [86], and video + hand gesture overlay [38].…”
Section: Multimodal Recording and Annotationmentioning
confidence: 99%
See 1 more Smart Citation
“…With a voice recording, message producers can leverage paralingual cues (e.g., inflection, pause timing, energy) for conveying equivocal and complex ideas [13]. Speech annotation/commenting, thanks to its rich, nuanced expressivity, has been widely adopted in different applications including online discussions [52] or document review [55]. Inspired by media richness theory [18] and the conceptual framework of deictic gestures [17], several multimodal annotation systems have tried to enrich communication and collaboration by combining multiple face-to-face inspired modalities, such as inking + speech [75,83], inking + gesture + speech [86], and video + hand gesture overlay [38].…”
Section: Multimodal Recording and Annotationmentioning
confidence: 99%
“…collaborators express and understand nuanced, complex ideas effectively [13,55,87]. On the other hand, as Grudin pointed out, when consuming, browsing recorded speech can be tedious and slow for the consumer [34], and, when producing, it is known that multimodal recordings are harder to revise than text [72] and can provoke self-consciousness [1,52].…”
Section: Introductionmentioning
confidence: 99%
“…Chalfonte and Kraut have also shown that spoken annotation's expressiveness and richness are more suitable for describing structural or semantic issues in comparison with written annotation [3,8]. Furthermore, Neuwirth et al found that speaking, when compared with writing, generates more detailed explanations and nuance that can lead to better perceptions of comments at the receiving end [16].…”
Section: Speechmentioning
confidence: 99%
“…In formal learning environments, instructors recommend the use of mitigating language, such as praise or affirmation, before or after negative feedback to improve its receptivity [2,4,16,23,37]. Similar techniques are less applicable in online environments, where the feedback is often composed by multiple independent providers and platform designers have limited control over the composition process.…”
Section: Introductionmentioning
confidence: 99%